STRATEGI TINDAK TUTUR JURU BICARA TIM KAMPANYE NASIONAL DALAM ACARA “DUA ARAH” DI KOMPAS TV - Ikromal Hasin; Akhmad Sofyan; Edy Hariyadi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
Presidential Election is a democratic party to elect new leaders. A spokesperson is needed to attract the public to choose the candidate pairs who compete to win the party. A spokesperson for TKN-Jokowi's National Campaign Team (Indonesian: Tim Kampanye Nasional) is one example of a spokesperson who carried out this task. This article aims to discuss the national campaign team's speech acts strategy in Kompas TV program entitled